Interpretasi Sikap “Datuk Maringgih” dalam Novel “Kasih Tak Sampai” pada Karya Tari "Sasau" - Harlen, Windy Avrilia; Osmond, Dony; Metro, Wardi; Ariastuti, Idun (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The dance work "Sasau" is inspired by the character of Datuk Maringgih in Marah Rusli's novel "Siti Nurbaya: Kasih Tak Sampai," which represents a toxic leader. This leadership trait was chosen because it is still highly relevant to contemporary social phenomena. The artist focused on interpreting the leader's arbitrary behavior, which negatively impacts the surrounding environment, and then translated it into a group choreography divided into three moods. The methods used in the creation process included data collection, exploration, improvisation, forming, and evaluation. The performance was performed by seven dancers—four female dancers and three male dancers—with a dramatic style centered on social themes. The musical accompaniment was developed through a combination of traditional Minangkabau instruments and the latest digital audio technology to support the dramatic flow, in line with the artist's concept.